Aquatic macrophyte diversity of the Pantanal wetland and upper basin - Pott,VJ. (2011)
This is a short review of the state of the art concerning diversity of aquatic macrophytes and the main aquatic vegetation types in the Brazilian Pantanal wetland and upper watershed. There are ca. 280 species of aquatic macrophytes on the Pantanal floodplain, with scarce endemism. On the upper watershed, Cerrado wetlands (veredas) and limestone springs have a distinct flora from the Pantanal, with twice the species richness. As a representative case of aquatic habitats influenced by river flood, some primary data are presented for the Pantanal Matogrossense National Park and associated Acurizal Preserve, analysing the floristic similarity among aquatic vegetation types. We comment on problems of conservation and observe that Panicum elephantipes Nees is one of the few natives to compete with the invasive Urochloa arrecta (Hack. ex T. Durand & Schinz) Morrone & Zuloaga.